Pengaruh Efisiensi Modal Kerja “Working Capital Turnover” Dan Debt To Equity Terhadap Profitabilitas “Return On Equity” Pada Beberapa Perusahaan Manufaktur Industri Food And Bevereges Yang Terdaftar Di Bursa Efek Indonesia (Bei) Periode 2009-2013 - Deri Zul Safar (Jurnal Akuntansi UMMI, 2020)
Influence Efficiency Working Capital "Working Capital Turnover" and the Debt to Equity To Profitability "Return on Equity" at the company's industry Food and Bevereges listed on the Indonesia Stock Exchange (BEI) in the period 2009-2013 (Adviser Elan Eriswanto, SE, MM and Tanti Agustiani , M. Hum). This study aims to to assess the extent to which the influence of efficiency working capital “working capital turnover” and debt to equity to profitability “return on equity“ good simultaneously and partial . The object of this study is the working capital turnover, debt to equity and return on equity at the Food and Bevereges industry companies listed on the Indonesian Stock Exchange (BEI) in the period 2009-2013, data were analyzed on the object of the study are the financial statements of the nine industry Food and Bevereges listed on the Indonesia Stock Exchange (BEI) in the period 2009-2013. This study uses a quantitative method with descriptive approach and associative regression analysis showed, which simultaneously Working Capital and Debt to Equity Turnover significant effect on Return on Equity of 8:06%, while the remaining 91.93% influenced by other factors. In partial Working Capital Turnover was no significant effect on Return on Equity with ttcount 1648 <ttable 2.04523 and Debt to equity is also partially no significant effect on Return on Equity with tcount -0337 <ttable 2.04523, which means secera overall is that the size of the company's return on equity is less affected by Turnover Working Capital and Debt to equity. And simultaneously the size of return on equity is less affected by Turnover Working Capital and Debt to equity with a value of Fcount 1,447 <Ftabel 3.284918.